RESPONSE RATES TO STANDARD INTERFERON TREATMENT IN HCV GENOTYPE 3A - Qureshi, Saleem; Batool, Uzma; Iqbal, Musarrat; Qureshi, Omarah; Kaleem, Rao; Aziz, Hina; Azhar, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Chronic Hepatitis C infection infects almost 130 to 170 million or approximately 2.2-3% of world’s population. HCV is one of the main causes of chronic liver disease leading to progressive liver injury, fibrosis, cirrhosis and liver cancer. It is also one of the leading indications for liver transplantation worldwide. The objective of the study was to determine the response of treatment with standard Interferon and Ribazole in treatment naÃ¯ve Hepatitis C infected patients. Methods: This quasi-experimental study was carried out at the Department of Medicine, KRL General Hospital Islamabad, from January 2003 to January 2005. A total of 250 patients were enrolled in this descriptive study. All patients were anti HCV positive, PCR positive for HCV RNA and had 3a genotype. A non-probability purposive sampling technique was applied to collect data. After taking a written and informed consent; specially designed performa containing the patient profile, family transmission, and baseline laboratory values was filled. Patients were treated with a set protocol of Interferon plus Ribavarin therapy (IFN alpha 2a, 3 mIU thrice weekly for 24 weeks plus Ribavarin 1,000 to 1,200 mg/day) for six months. Chi-Square tests were used to analyse the data. Primary end point was a sustained virological response (SVR) that is response assessed after six months of completion of treatment. Results: Response rates to standard Interferon plus Ribazole therapy were studied over two years period. Out of the total of 250 patients, 60 patients were excluded; as 30 patients did not meet inclusion criteria, 23 patients were lost to follow. Seven patients declined treatment. Out of the190 patients, 155 (81.6%) achieved End of Treatment Complete Response (EOTCR) whereas 35 (18.4%) were nonresponders (NR). These 155 patients, who showed complete response were followed for six months after the treatment to assess sustained viral response, which was seen in 112 (72.25%) patients whereas 43 (27.7%) were relapsers. Response rates were co-related with gender, baseline ALT and necro-inflammatory stage assessed by liver biopsy, probable risk factors and family history. Conclusion: Management of Hepatitis C with genotype 3a, with standard Interferon and Ribazole for six months showed lower SVR compared to that reported in previous international and local data. Keywords: HCV, Interferon, Response Rates, SVR.